2021
DOI: 10.1136/bcr-2021-242590
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric primary cough headache with internal jugular phlebectasia

Abstract: Primary cough headaches (PCHs) are mainly observed in people aged >40 years, but cough-induced headaches are potentially symptomatic in children. We report a case of a child diagnosed with PCH without an intracranial disease. A 7-year-old boy presented with cough due to pertussis and powerful cough-induced headaches. No brain abnormalities were detected, but the right side of his neck was observed to swell. Echo examination confirmed right internal jugular vein dilatation during a Valsalva manoeuvre, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…This could potentially have contributed to the discovery of right-sided phlebectasia. The constant stress from repeated bouts of coughing led to increased intrathoracic and intra-abdominal pressure, resulting in transient retrograde venous flow [ 10 ]. In fact, during coughing, the intrathoracic pressure increases from 100-250 mmHg, depending on the severity, to as high as 300 mmHg in adults [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could potentially have contributed to the discovery of right-sided phlebectasia. The constant stress from repeated bouts of coughing led to increased intrathoracic and intra-abdominal pressure, resulting in transient retrograde venous flow [ 10 ]. In fact, during coughing, the intrathoracic pressure increases from 100-250 mmHg, depending on the severity, to as high as 300 mmHg in adults [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology is unclear [2]. A systematic review performed on this condition [1] identified 97 articles describing 206 pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology is unclear. 2 A systematic review performed on this condition 1 identified 97 articles describing 206 pediatric patients. Nonetheless, it remains a poorly known condition, usually diagnosed from a few months to several years after the onset of symptoms.…”
Section: Introductionmentioning
confidence: 99%